Improving the investigative approach to polycythaemia vera: a critical assessment of current evidence and vision for the future. Issue 8 (August 2021) - Ronner, Lukas; Venugopal, Sangeetha; Moshier, Erin; Mascarenhas, John
Summary: Polycythaemia vera is a challenging disease to study given its low prevalence and prolonged time-to-event for important clinical endpoints such as thrombosis, progression, and mortality. Although researchers in this space often rise to meet these challenges, there is considerable room for improvement in the analysis of retrospective data, the development of risk-stratification tools, and the design of randomised controlled trials. In this Viewpoint, we review the evidence behind the contemporary approach to risk stratification and treatment of polycythaemia vera. Frameworks for using data more efficiently, constructing more nuanced prognostic models, and overcoming challenges in clinical trial design are discussed.